Mandibular Implant Overdenture Treatment: Consensus and Controversy - David R. Burns, DMD (Blackwell Synergy, 2000)
A literature review of implant overdenture treatment for the edentulous mandible is presented. The report focuses on the knowledge base for this treatment modality, in an effort to distinguish between areas that are well characterized and enjoy a higher level of consensus among practitioners as compared with those that are more controversial and not clearly understood